2004
DOI: 10.1002/pssc.200405502
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic effects on transition metal doped Ga 2 O 3 ‐based semiconductor

Abstract: PACS 61.66.Fn, 75.50.Pp, 76.80.+y Single phases of polycrystalline Ga 2-x TM 2x O 3 (x=0.00, 0.05, 0.10) powder samples were prepared by a standard solid-state reaction method. The X-ray diffraction patterns of the Ga 2-x TM x O 3 (x=0.00, 0.05, 0.10) powders showed no detectable TM phase. All the peaks for the X-ray diffraction patterns of samples belong to the monoclinic (C2/m) lattice of β-Ga 2 O 3 . The lattice parameters for the Ga 1.8 Fe 0.2 O 3 and Ga 1.8 Mn 0.2 O 3 are found to be a 0 = 12.264 Å, b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…Because of the oxidation of Ga as well as of Fe the layer can be regarded as Ga 2 O 3 with inclusions of some iron oxide. This result is in contrast to the results from Lee et al, 23 where Fe doped ␤-Ga 2 O 3 was found to be ferromagnetic.…”
contrasting
confidence: 99%
“…Because of the oxidation of Ga as well as of Fe the layer can be regarded as Ga 2 O 3 with inclusions of some iron oxide. This result is in contrast to the results from Lee et al, 23 where Fe doped ␤-Ga 2 O 3 was found to be ferromagnetic.…”
contrasting
confidence: 99%
“…Hojo et al [11] and Lee et al [10] reported the observation of ferromagnetism in the Fe 3 þ doped β-Ga 2 O 3 . In the Mn 2 þ doped β-Ga 2 O 3 , however, Song et al [12] suggested a strong antiferromagnetic superexchange interaction between the doped Mn 2 þ ions.…”
Section: Introductionmentioning
confidence: 99%
“…In the monoclinic structure of β-Ga 2 O 3 , the Ga 3 þ ions are accommodated in the non-equivalent tetrahedral (A) and octahedral (B) sites. The properties of β-Ga 2 O 3 , such as transportation [4][5][6][7][8][9], magnetism [10][11][12][13][14], and photoluminescence [15][16][17][18], can be greatly affected by the substitution of Ga 3 þ ions with the doped impurities. The previous investigations on the doping of β-Ga 2 O 3 indicate that compared with the Ga 3 þ ion ( $ 0.62 Å), the doped ion with a larger radius, such as Ti 4 þ [6], Cr 2 þ [19,20], Mn 2 þ [21,22], Fe 3 þ [23,24], In 3 þ [25,26], Er 3 þ [27], and Eu 3 þ [28], tends to occupy the B sites, while the doped ion with a smaller radius prefers to sit at the A site, such as Be 2 þ [26], and Si 4 þ [14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the wide gap semiconductors such as ZnO, GaN, and Ga 2 O 3 doped with manganese are found to have high Curie temperature (Dietl et al 2000;Song et al 2006). Specifically, experimental studies on Ga (2-2x) Mn 2x O 3 (x = 0.05, 0.10) polycrystalline material have found a direct relationship between the dopant concentration and the magnetization effects (Lee et al 2004). It was then suggested that a detailed analysis of local environment of Mn is necessary to understand the increase in the magnetization effect with Mn concentration in the oxide lattice.…”
Section: Introductionmentioning
confidence: 99%